Isoprenoids from Rhaponticum carthamoides (Willd.) Iljin and Rhaponticum serratuloides (Georgi.) Bobr (International Journal of Biology and Chemistry, 2024)
The article presents the results of a chemical study of Rhaponticum carthamoides (Willd.) Iljin. and Rhaponticum serratuloides (Georgi.) Bobr., which are of interest as sources of new adaptogenic, anabolic, and antiparasitic drugs; a method for complex chemical processing of the raw materials of the abovementioned plants has been proposed. The structure of new sesquiterpene lactones raposerine, raserolide, 15-deacetylraposerine, and raserine has been isolated and established. The content of pharmacologically active ecdysterone in various organs of the studied Rhaponticum species is discussed according to the phenological phases of plant development. The antiparasitic, antiviral activity and cytotoxicity of the isolated compounds were determined.